Phosphatase and Tensin Homolog Mutation in Immune Cell Infiltration and Clinicopathological Features of Low-Grade Gliomas - Feng, Peng; Li, Zhenqing; Li, Yuchen; Zhang, Yuelin (Frontiers in Molecular Biosciences, 2020)
Phosphatase and tensin homolog (PTEN) genes are found frequently in mutated genes of low-grade gliomas (LGG) of the brain and are associated with poor prognosis and survival rate. This study analyzed Ribonucleic acid sequencing using LGG datasets obtained from The Cancer Genome Atlas datasets to confirm crucial signaling pathways and genes connected to the PTEN mutation and then assessed the influence of immune cell infiltration and PTEN status. The GO and KEGG were analyzed, and the DEGs were enriched in categories connected with multiple metabolic progressions and cell division. There were 10 genes classified by degree and confirmed as hub genes from the protein–protein interaction network. We drafted a way to assess the influence of the PTEN mutations on prognosis, overall survival, and Messenger Ribonucleic acid (mRNA) expression. Moreover, the histological stage was significantly associated with PTEN expression levels. In addition, the PTEN mutation was associated with an abundance of B cells, neutrophils, macrophages, dendritic cells, and CD8+ T cells during tumor infiltration. The results showed that the patients who carried the PTEN mutation were connected with a poor prognosis in LGG, and immune cell infiltration occurred at the mRNA expression level. Therefore, the results suggested that multiple genes and the signaling pathways might play a key role in LGG associated with PTEN mutations, and could provide PTEN mutation alternative targets and strategies for personalized treatment of LGG.